Mosques as a symbol of Islamic civilization: its role and function - Sulaiman, Kabuye Uthman (International Institute for Muslim Unity, International Islamic University Malaysia, 2015)
It is undeniable that every civilization has a symbol that makes it distinct from other civilizations. It is also undeniable that many civilizations have passed and their symbols disappeared but the Islamic civilization and its symbol are endurable. The symbol of Islamic civilization is the mosque. It is one of the oldest institutions that continue to exist in every society and it will continue to exist on earth throughout the ages to come. The mosque plays a very important role in Muslims’ development particularly in the spiritual realm. Thus it is contended that “the mosque has to be at the heart of all of life’s positive and constructive activities, in order to shape righteous generation.” (Muhammad, 1996, p.5). The mosque is not only a place where Muslims regularly meet to perform the five obligatory salat together but also a place where they regularly meet to learn together and to share their lives with one another, to encourage and console one another, and to help the needy. According to Qureshi, mosque is an institution through which ‘the Prophet succeeded in reforming the people individually and collectively.” (Qureshi, 1990, pp.135-136). This paper seeks to elaborate the role of the mosque in the establishment of the relationships between man and Allah and man and his fellow humans. These two relationships, also known as the vertical and horizontal relationships, need to be established to have a just and harmonious society